Mathematical sciences with multidisciplinary applications : in honor of Professor Christiane Rousseau. And in recognition of the mathematics for planet Earth initiative /: in honor of Professor Christiane Rousseau. And in recognition of the mathematics for planet Earth initiative. (2016) - Unknown
No abstract available